The effects of intergovernmental transfers on the local fiscal incentives of Brazilian municipalities - Pedro Jorge Holanda Alves; Jevuks Matheus de Araujo (Journal of Government and Economics (JGE), 2024)
The objective of this work is to analyze the impact of fiscal decentralization on the behavior of Brazilian municipal policymakers. This work uses the first three cutoffs of the transfer rules of the Municipal Participation Fund (FPM) and applies a regression discontinuity designs (RDD) to capture the effects that have impacted municipal budget rates from 2013 to 2016. The comportment hypothesis is that transfer gains can generate (a) perverse incentives, if the gains are earmarked for personnel and administrative expenses or if they decrease revenue, or (b) beneficial incentives, if the main gains are spent on education or health. The results found for the estimates of the data panel model suggest that an increase in exogenous revenue generates a significant increase only in spending on administrative and sports and leisure functions and that the possible channel for this increase in expenses should be aimed at increasing the number of employees with commissioned position. These results indicate that the transfers generate only perverse incentives. This article explores how local managers allocate their resources according to their additional budget. Unlike the other works, we look for the mayor's behavior in relation to spending on the employment of commissioned civil servants, which can lead to perverse incentives.
Keywords: E62; H72; C26; 330; FPM; Municipalities; RDD